Institute of economics and management in oil and gas industry – the first among equals! - Гораль, Л. Т. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
1